Цагаан овооны эртний түрэг бичээсийг дахин нягтлах нь: Re-examining the ancient Turkic inscription of Tsagaan Ovoo - Б., Хасбаатар (Mongolian Studies, 2023)
“Tsagaan ovoonii bichees/Inscriptions of White ovoo” is the only ancient Turkic inscription found from Inner Mongolia and it has the meaning “Sahigchyin bichig minu” consisted of 11 letters as “qur(ï)čïn bit(i)g(i)m”. No certain personal names, historical events and dates were mentioned in this inscription, thus it is impossible to determine its written date. The further studies are in progress.